Reciprocity models revisited: intention factors and reference values - Janna Hinz; Andreas Nicklisch; Mey-Ling Sommer (International Journal of Game Theory, 2024)
We present a test of the two most established reciprocity models, an intention factor model and a reference value model. We test characteristic elements of each model in a series of twelve mini-ultimatum games. Results from online experiments show major differences between actual behavior and predictions of both models: the distance of actual offers to the proposed reference value provides a poor measure for the kindness of offers, while a comparison of offers with extreme offers as suggested by the intention factor model makes offers indiscriminable in richer settings. We discuss possible combinations of both models better describing our observations.
Keywords: C52; C72; C91; 330; Experiments; Intentions; Mini-ultimatum game; Reference value; Reciprocity models